An increasing number of hand injuries in an elderly population – a retrospective study over a 30-year period - Hans-Eric Rosberg; Lars B. Dahlin (BMC Geriatrics, 2018)
Abstract Background Both the number and the proportion of elderly people in the society increase. The number of elderly subjects with a disability due to a disease has decreased resulting in more active elderly. Therefore, an increase in numbers of injury in the elderly population can be expected; a hypothesis that was investigated in the present study. Methods Two-hundred sixteen patients with an age of > 65 years, and admitted to a hand surgery ward with a hand injury, were retrospectively collected at four different 2-years periods over a 30 years time (1980–81 to 2010–11). Information about patient gender, age at injury, injury place and mechanism (s), injured structures, duration of hospital stay, number of out patient visits and rehabilitation visits as well as social status was collected. The injuries were classified with the Modified Hand Injury Severity Score (MHISS). Results Most injured patients were men (72%) and the number of patients who reported to be healthy significantly decreased (67% to 18%) during the study period. The number of injuries increased over the study period (n = 24 to n = 83/2-year period). Outside home was the most common injury place and a saw or a fall was the most frequent injury mechanism. Several fingers were most often injured. The majority of the injuries were classified to be Minor or Moderate (MHISS) and a fracture was the most common injured structure. Conclusions We found an increased number of hand injuries over a 30-year period in combination with a decrease in patients reported health treated at a hand surgery ward. Further studies regarding hand trauma in the elderly population will be valuable for future prevention and rehabilitation of this patient group.